A identidade sertaneja em Goiás: um estudo a partir dos elos entre a geografia e a literatura de Bernardo Élis - BRAGA, Helaine da Costa (2009)
This essay presents a reading of the country lifestyle in Goias for the cultural rescue of the past. The reflections result from bonds between Geography and Literature. The intention of this research is to highlight the cultural space contents, extracting from the bond between scientific language and artistic language, the most significant elements in the relationship between subjects and territory. Such elements are appreciated by the humanist chain of Geography and are present in the literature of the Goiano writer Bernardo Elis. From his work to an interlocution of Geography, the short-stories books Ermos e Gerais , Caminhos e Descaminhos and Veranico de Janeiro were chosen. The geographic interpretation of short-stories such as Rosa, A Enxada, Moagem, Ontem Como Hoje, Como Amanhã, Como Depois, among others, takes into consideration the interaction between the countrymen and the nature of the Brazilian interior vegetation, the social and work relations, the social representations, the symbolic territorial appreciation and the landscape formations. These categories of analysis allowed a route crossing within the cultural backland identity: from its construction in a rural context to its recreation in an urban context. Nowadays, there is a genre for the cultural backland identity. It is translated by readings that people from rural origin place within the urban space. The communication between symbols, traditional and modern values present in life experience and territorial landscape points out that giving a new meaning to culture does not discard the essential characteristics of the backland. The meanings of the current country lifestyle experience were able to be understood because, in the three chapters which compose the essay, Bernardo Elis‟ literature is about clarifying the complexity of the human being within the regional culture scenario.